2017
DOI: 10.1021/acsenergylett.7b00179
|View full text |Cite
|
Sign up to set email alerts
|

Crystallite Size Control of Prussian White Analogues for Nonaqueous Potassium-Ion Batteries

Abstract: Nonaqueous potassium-ion batteries have emerged as possible lowcost alternatives to Li-ion batteries for large-scale energy storage, owing to their ability to use graphitic carbon as the negative electrode. Positive electrode materials remain a challenge. Here, we report control of the crystal dimensions of the Prussian white hexacyanoferrate (HCF), K 1.7 Fe[Fe(CN) 6 ] 0.9 , using solution chemistry to obtain either nano, submicron, or micron crystallites. We observe a very strong effect of crystallite size on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
270
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(280 citation statements)
references
References 45 publications
9
270
1
Order By: Relevance
“…[11] Here, we found that simply replacing the potassium citrate with potassium chloride gave uniform and decreased particle size distribution ( Figure S1, Supporting Information). Meanwhile, the shape and size affect both the number and activity of reaction sites in intercalation electrodes.…”
Section: Resultsmentioning
confidence: 77%
“…[11] Here, we found that simply replacing the potassium citrate with potassium chloride gave uniform and decreased particle size distribution ( Figure S1, Supporting Information). Meanwhile, the shape and size affect both the number and activity of reaction sites in intercalation electrodes.…”
Section: Resultsmentioning
confidence: 77%
“…[34] Typically, 5.0 g potassium citrate (K 3 C 6 H 5 O 7 , Aldrich) and 1.68 g iron(II) sulfate pentahydrate (FeSO 4 ⋅5H 2 O, Aldrich) were added into 100 mL water. [34] Typically, 5.0 g potassium citrate (K 3 C 6 H 5 O 7 , Aldrich) and 1.68 g iron(II) sulfate pentahydrate (FeSO 4 ⋅5H 2 O, Aldrich) were added into 100 mL water.…”
Section: Methodsmentioning
confidence: 99%
“…[41,42] This is induced by Zn insertion into the lattice to form a Zn-adequate framework. The structural transition can be detected from the changes of XRD pattern (011) and (200) reflections with peaks at 17.4° and 18.4°, respectively.…”
Section: Structure Evolution and Morphology Analysis At Different Depmentioning
confidence: 99%